2017
DOI: 10.1097/acm.0000000000001255
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Trainee and Staff Perceptions of Patient Safety Culture

Abstract: Generally, trainees had comparable to more favorable perceptions of patient safety culture compared with staff. They did identify opportunities for improvement though. Hospitals can use perceptions of patient safety culture to complement CLER visit reports to improve patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 18 publications
3
19
0
1
Order By: Relevance
“…Of these, 157 studies were excluded for various reasons, such as mismatch with the inclusion criteria, wrong study design (e.g., validation study, quasi-experimental design), mixed population, wrong focus of the study, or full text not available (see Supplementary File 3 ). Finally, 31 studies meeting the inclusion criteria were included [ 13 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] (see Supplementary File 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 157 studies were excluded for various reasons, such as mismatch with the inclusion criteria, wrong study design (e.g., validation study, quasi-experimental design), mixed population, wrong focus of the study, or full text not available (see Supplementary File 3 ). Finally, 31 studies meeting the inclusion criteria were included [ 13 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] (see Supplementary File 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies fulfilled at least four of the five quality appraisal criteria [ 22 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 33 , 35 , 37 , 38 , 39 , 40 , 43 , 45 , 48 ], and five studies met all criteria [ 28 , 35 , 37 , 39 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It would be reasonable to think that they would be involved or witness several patient safety events, either directly or indirectly. Schectman, et al, and Bump, et al, found trainees to have a more favorable perception of patient safety culture and higher reporting than senior physicians [8,9]. However, multiple studies have shown that residents are not frequent event reporters either.…”
Section: Introductionmentioning
confidence: 99%